Critical review of axillary recurrence in early breast cancer - Castaneda, Carlos (2018)
Around 2% of early breast cancer cases treated with axillary lymph node dissection (ALND) underwent axillary recurrence (AR) and it has a deleterious effect in prognosis. Different scenarios have incorporated Sentinel Lymph Node (SLN) Biopsy (SLNB) instead of ALND as part of the standard treatment and more effective systemic treatment has also been incorporated in routine management after first curative surgery and after regional recurrence. However, there is concern about the effect of SLNB alone over AR risk and how to predict and treat AR. SLN biopsy (SLNB) has been largely accepted as a valid option for SLN-negative cases, and recent prospective studies have demonstrated that it is also safe for some SLN-positive cases and both scenarios carry low AR rates. Different studies have identified clinicopathological factors related to aggressiveness as well as high-risk molecular signatures can predict the development of locoregional recurrence. Other publications have evaluated factors affecting prognosis after AR and find that time between initial treatment and AR as well as tumor aggressive behavior influence patient survival. Retrospective and prospective studies indicate that treatment of AR should include local and systemic treatment for a limited time.